Association between psychological measures with inflammatory anddisease-related markers of inflammatory bowel disease. (3rd July 2017) - Abautret-Daly, Áine; Dempsey, Elaine; Riestra, Sabino; de Francisco-García, Ruth; Parra-Blanco, Adolfo; Rodrigo, Luis; Medina, Carlos; Connor, Thomas J.; Harkin, Andrew
Abstract: Objective: This study aimed at investigating the associations between inflammatory mediators, symptoms and psychological disturbances in inflammatory bowel disease (IBD) patients. Methods: IBD patients and patient controls were examined during a single visit to a gastroenterology clinic. Disease activity was assessed using the Mayo index for ulcerative colitis (UC), inflammatory bowel disease questionnaire (IBDQ), Crohn's disease activity index (CDAI) and Crohn's disease endoscopic index of severity (CDEIS). Gene expression of inflammatory mediators were measured in intestinal biopsies and whole blood samples along with circulating concentrations of interleukin (IL)-6, interferon (IFN)γ, C-reactive protein (CRP), kynurenine and tryptophan. Validated depression, anxiety and quality of life scores were used to assess psychological well-being. Results: Patients who were symptomatic had the highest depression and anxiety scores, together with increased intestinal expression of IL-1β, IL-6 and matrix metalloproteinase-9, increased circulating IL-6 and CRP, and an increased circulating kynurenine:tryptophan ratio. Increased Hamilton depression (HAM-D) scores in IBD patients were observed independent of the psychological impact of acute symptoms. Conclusions: Active IBD is associated with symptoms of depression and anxiety and with a raised circulating inflammatory mediator profile. Patients with active IBD exhibiting psychological symptoms should undergo psychological evaluation to ensure the psychological aspects of the condition are considered and addressed.